Real Estate Prices, Inflation, and Health Outcomes: Evidence From Developed Economies - Bao, Wensheng; Tao, Ran; Afzal, Anees; Dördüncü, Hazar (Frontiers in Public Health, 2022)
Population health is a key pillar of the fast-growing economies, but several challenges threaten it. This study scrutinizes the impact of real estate prices (housing rent) and inflation on population health by using advanced economies from 1996 to 2019. Health is measured by infant mortality rates and life expectancy at birth. The empirical outcomes show a positive and significant effect of housing rent on the infant mortality rate. In contrast, housing rent improves life expectancy. We also find that an increase in inflation positively affects the infant mortality rate and has a negative effect on life expectancy. GDP and health expenditure tend to improve health by increasing life expectancy and reducing the infant mortality rate. However, unemployment is harmful effects on population health. This study recommends that healthcare practitioners consider the housing market and inflationary pressure.